ChemInform Abstract: Access to Cyclobutene‐Fused Azepines Through Au‐Catalyzed Cycloisomerization of Stable Alkyne Tethered Ketene N, N‐Acetals. Issue 48 (2nd December 2014) - Nayak, Sanatan; Ghosh, Nayan; Sahoo, Akhila K.
Abstract The synthesis of N‐protected alkyne‐tethered ketene‐N, N‐acetals from N‐protected propargylamines and 3‐bromopropiolates is demonstrated for the first time.